The Inﬂuence of Spiritual Leadership on Organizational Culture at Bank Syariah Mandiri Branch Office and Sub Branch Office Depok - Abdul Jabbar; Retno Kusumastuti (Policy & Governance Review, 2017)
This research aims to examine and analyze the inﬂuence of spiritual leadership on organizational culture implemented by Bank Syariah Mandiri (hereinafter will be referred as “BSM”) Branch Ofce and Sub Branch Ofce Depok. Spiritual leadership can be measured by using the concept of spiritual leadership developed by Fry (2003) with fve dimensions, namely: vision, altruistic love, hope/faith, meaning/calling, membership, and organizational culture as measured by the ETHIC (Excellence, Teamwork, Humanity, Integrity, and Customer Focus) dimensions in Bank Syariah Mandiri’s organizational culture. This research utilized a quantitative approach wherein research data were collected through survey conducted to all employees in the BSM Branch Ofce and Sub Branch Ofce Depok, with 55 respondents being involved in this research. The research data were subsequently analyzed by using descriptive statistics analysis and simple linier regression analysis. The results of this research show that spiritual leadership of the Head of BSM Branch Ofce Depok has a 56 percent positive eﬀect on the implementation of ETHIC organizational culture in BSM.